PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PKN DI KELAS IV SD NEGERI 02 TALAGO SARIAK KECAMATAN PARIAMAN TIMUR KOTA PARIAMAN - Rosmiwati S. Pd (Menara Ilmu, 2016)
Based on preliminary studies carried out in the fourth grade elementary school 02 Talago Sariak Kota Pariaman Pariaman District East shows that learning is conducted in the conventional Civics where teachers still use media that is limited to textbooks and learning assessment only on the cognitive domain. This causes less active learners in the learning process and learning results obtained are low. To improve the learning outcomes of students in the learning Civics held a classroom action research. The purpose of this study was to describe how the design, implementation and assessment of learning civics by using audio-visual media.This research is a classroom action research with qualitative and quantitative approaches. In practice, this study consisted of two cycles undertaken collaboratively with Civics teacher. Each cycle consists of planning, implementing measures are accompanied observations and reflections on each cycle. The research was conducted in the second semester of the school year 2014/2015 in SD Negeri 02 Talago Sariak Kota Pariaman Pariaman District East with the subject of the study were all fourth grade students terteliti. The research data was collected through observation, interviews, field notes, documentation and test results.The results of data analysis showed that the use of audio-visual media can improve learning outcomes of students in learning in fourth grade Civics State 02 Talago Sariak Kota Pariaman Pariaman District East. It is seen from (1) Results of learners in cognitive an increase of the average value of 7.1 in the first cycle to 8.0 in the second cycle, (2) the affective domain increased from an average value of 7.8 the first cycle to 8.5 in the second cycle, and (3) on psychomotor increased from an average value of 6.4 in the first cycle to 7.9 in the second cycle. Seeing the results of this study, the class action research in the use of audio-visual media in Civics learning needs to be applied and developed in order to improve the quality of education in the future. Keywords: Media Audio Visual, Results Learning, Learning Civics